Kurt W. Rothschild (1914 - 2010). A modest and upright character with an outstanding publication record - Wilfried Altzinger (Intervention. European Journal of Economics and Economic Policies, 2011)
First paragraph: With the death of Kurt W. Rothschild on 15 November 2010 at the age of 96, Austria has lost, without doubt, one of her most thoughtful and original economic thinkers of the past century. He has been contributing to economics through a large number of publications in several fields over a period of nearly 70 years. A recent count lists 25 books, 120 papers in scholarly Journals, 115 contributions to collective volumes, and 140 book reviews. However, it was not only his outstanding scientific performance which made Rothschild unique, moreover it was his modesty and his upright character combined with his openness and unusual analytical tolerance which made him one of the most respected speakers in public forums, as well as an enjoyable conversational partner at more private occasions. There was never any moment where one did not excitedly listen to his well-founded and conclusive arguments. It was indeed not only his public performance which impressed scholars, students and ordinary people alike. It was in particular the coherence of his public and private life which made him impressively credible.
Keywords: 330